How do students experience choice? Exploring STEM course-offerings and course-taking patterns in Texas charter and non-charter public schools - David, Bernard G.; Marder, Michael; Marshall, Jill; González-Howard, María (Education Policy Analysis Archives, 2020)
Charter schools are positioned by proponents as a key component of reform efforts striving to expand school choice. Proponents argue that charter schools have the flexibility to experiment with novel curricular and instructional models outside the constraints of the traditional public education system, and therefore have the potential to transform students’ experiences. Influential reports over the last three decades have highlighted the need to improve students’ preparation in STEM, and charter schools have emerged as a reform with the potential to do so. This work uses methods from social network analysis and logistic regression to investigate how course-taking patterns in Texas charter and non-charter schools either promote or constrain student engagement within the STEM disciplines by: 1) exploring STEM course offerings in Texas charter and non-charter public secondary schools; and 2) identifying students’ STEM course-taking patterns in these schools. Findings suggest charter schools are less likely than non-charter public schools to offer STEM courses tailored for special education students and that charter school students’ course-taking patterns tend to be either slightly more advanced or more basic than the course-taking patterns of students in non-charter schools. In addition, students in charter schools tend to be more mobile (e.g., transfer between schools) than students in non-charter public schools.